Notice of Joint Meeting Between Camarillo and Oxnard Airport Authorities and a Summary of Recommended Actions April 8, 1999 - Dick Maggio:::::: (1999)
The agenda for a meeting between the Camarillo Airport Authority and the Oxnard Airport Authority. Includes a brief speech made by Dick Maggio and a summary of recommended actions in regards to the F.A.R. Part 150 Noise Study.